The innovation imperative of Ukrainian enterprises development - Ivashkiv, Yaroslav; Sobko, Yaroslav (Herald of Economics, 2025)
Introduction. Innovation being an imperative serves as the main factor in ensuring a way out from crisis situations, sustainable development of enterprises and economic growth at the micro level. The transformation of innovation ecosystems under the impact of digitalization, is aimed at modernizing the innovation environment through the development of innovation park formations, the introduction of new forms of entrepreneurship and startup business, and the internationalization of entrepreneurial activity, which is designed to ensure the revival of innovative activity of enterprises.Purpose. The purpose of the article is to identify the prerequisites and justify the feasibility of strengthening the innovation imperative of Ukrainian enterprises development.Results. The essence of the “innovation imperative of enterprise development as a dominant concept in the conditions of transformations of business ecosystems, which explains innovation and systematizes the factors ensuring economic growth at the micro level” is revealed. The dynamics of innovative activity of Ukrainian enterprises were analyzed, trends were constructed and factors that determined it in 2000–2024 were identified to assess the effectiveness of organizing innovative activity at the micro level. The socio-economic feasibility of strengthening the innovative imperative in the development of Ukrainian enterprises based on the revival of innovative activity of enterprises was grounded.Conclusions and prospects. Transformation of business ecosystems, search for ways out of permanent crisis phenomena, and post-war reconstruction of Ukraine will require a constant increase in the innovativeness of enterprises, due to the need to ensure the requirements of sustainable, inclusive and security development, which actualizes the feasibility of strengthening the innovative imperative. To ensure economic growth, enterprises should consistently search reserves for increase of their innovation, which is the subject for further scientific research